Structural insights into target DNA recognition and cleavage by the CRISPR-Cas12c1 system. Issue 20 (2nd November 2022) - Zhang, Bo; Lin, Jinying; Perčulija, Vanja; Li, Yu; Lu, Qiuhua; Chen, Jing; Ouyang, Songying
Abstract: Cas12c is the recently characterized dual RNA-guided DNase effector of type V-C CRISPR-Cas (clustered regularly interspaced short palindromic repeats and CRISPR-associated protein) systems. Due to minimal requirements for a protospacer adjacent motif (PAM), Cas12c is an attractive candidate for genome editing. Here we report the crystal structure of Cas12c1 in complex with single guide RNA (sgRNA) and target double-stranded DNA (dsDNA) containing the 5′-TG-3′ PAM. Supported by biochemical and mutation assays, this study reveals distinct structural features of Cas12c1 and the associated sgRNA, as well as the molecular basis for PAM recognition, target dsDNA unwinding, heteroduplex formation and recognition, and cleavage of non-target and target DNA strands. Cas12c1 recognizes the PAM through a mechanism that is interdependent on sequence identity and Cas12c1-induced conformational distortion of the PAM region. Another special feature of Cas12c1 is the cleavage of both non-target and target DNA strands at a single, uniform site with indistinguishable cleavage capacity and order. Location of the sgRNA seed region and minimal length of target DNA required for triggering Cas12c1 DNase activity were also determined. Our findings provide valuable information for developing the CRISPR-Cas12c1 system into an efficient, high-fidelity genome editing tool.